PVP-coated silver nanoparticles block the transmission of cell-free and cell-associated HIV-1 in human cervical culture - Lara Villegas, Humberto Herman; Ixtepan Turrent, Liliana del Carmen; Garza Treviño, Elsa Nancy; Rodríguez Padilla, María Cristina (2010)
Background: Previous in vitro studies have demonstrated that polyvinylpyrrolidone coated silver nanoparticles (PVPcoated AgNPs) have antiviral activity against HIV-1 at non-cytotoxic concentrations. These particles also demonstrate broad spectrum virucidal activity by preventing the interaction of HIV-1 gp120 and cellular CD4, thereby inhibiting fusion or entry of the virus into the host cell. In this study, we evaluated the antiviral activity of PVP-coated AgNPs as a potential topical vaginal microbicide to prevent transmission of HIV-1 infection using human cervical culture, an in vitro model that simulates in vivo conditions. Results: When formulated into a non-spermicidal gel (Replens) at a concentration of 0.15 mg/mL, PVP-coated AgNPs prevented the transmission of cell-associated HIV-1 and cell-free HIV-1 isolates. Importantly, PVP-coated AgNPs were not toxic to the explant, even when the cervical tissues were exposed continuously to 0.15 mg/mL of PVP-coated AgNPs for 48 h. Only 1 min of PVP-coated AgNPs pretreatment to the explant was required to prevent transmission of HIV-1. Pre-treatment of the cervical explant with 0.15 mg/mL PVP-coated AgNPs for 20 min followed by extensive washing prevented the transmission of HIV-1 in this model for 48 h. Conclusions: A formulation of PVP-coated AgNPs homogenized in Replens gel acts rapidly to inhibit HIV-1 transmission after 1 min and offers long-lasting protection of the cervical tissue from infection for 48 h, with no evidence of cytotoxicity observed in the explants. Based on this data, PVP-coated AgNPs are a promising microbicidal candidate for use in topical vaginal/cervical agents to prevent HIV-1 transmission, and further research is warranted